2003
DOI: 10.1021/bi034764d
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Scanning Mutagenesis in the αM3 Transmembrane Domain of the Torpedo californica Acetylcholine Receptor:  Functional and Structural Implications

Abstract: The functional role of the alphaM3 transmembrane domain of the Torpedo nicotinic acetylcholine receptor (AChR) was characterized by performing tryptophan-scanning mutagenesis at 13 positions within alphaM3, from residue M278 through I290. The expression of the mutants in Xenopus oocytes was measured by [(125)I]-alpha-bungarotoxin binding, and ACh receptor function was evaluated by using a two-electrode voltage clamp. Six mutants (L279W, F280W, I283W, V285W, S288W, and I289W) were expressed at lower levels than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 35 publications
(70 reference statements)
6
56
3
Order By: Relevance
“…In previous studies we have demonstrated that the tryptophan residue, the biggest amino acid, can be inserted along the ␣M3, ␣M4, ␤M3, ␥M3, and ␥M4 lipid-exposed domains of the AChR (25,27,(32)(33)(34)(35). Here, we provide both functional and structural interpretations for the ␣M3 TrpScanM in correlation with previous TrpScanM studies, photolabeling affinity studies (10,12), and the most recent T. marmorata AChR structure (6).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In previous studies we have demonstrated that the tryptophan residue, the biggest amino acid, can be inserted along the ␣M3, ␣M4, ␤M3, ␥M3, and ␥M4 lipid-exposed domains of the AChR (25,27,(32)(33)(34)(35). Here, we provide both functional and structural interpretations for the ␣M3 TrpScanM in correlation with previous TrpScanM studies, photolabeling affinity studies (10,12), and the most recent T. marmorata AChR structure (6).…”
Section: Discussionsupporting
confidence: 68%
“…Functional Interpretation of the ␣M3 Tryptophan Scanning-In contrast to our previous studies (25,27,(32)(33)(34)(35), we have found 6 mutations (␣F280W, ␣V285W, ␣S288W, ␣T292W, ␣V293W, and ␣I294W) that produce significant reductions in the AChR expression levels, suggesting a reduced efficiency of assembly and/or oligomerization of the AChR. Previously, 3-trifluoromethyl-3-(m-[ 125 I]iodophenyl)diazirine) photolabeling studies in the Torpedo californica AChR suggested that these residues are oriented toward the AChR interior, away from the lipid membrane (10).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations